Timing Matters ‐ Influenza Vaccination to HIV‐Infected Patients. Issue 8 (26th January 2016) - Glinka, ER; Smith, DM; Johns, ST
Abstract : Objectives: Patients with HIV infection vaccinated early in the flu season are more likely to contract influenza or influenza‐like illness (ILI) compared with those receiving late vaccination. It is known that antibody titres wane over time, particularly among individuals with HIV infection. It is unclear if the timing of influenza vaccination within the flu season affects the probability of an influenza infection later during the flu season. The aim of this study is to evaluate if there is a relationship between the timing of influenza vaccination and incidence of influenza or ILI in patients with HIV infection. Methods: A retrospective cohort study of HIV‐infected patients in care at the Department of Veterans Affairs San Diego Healthcare System was conducted from 1 September 2005 to 31 May 2013. Among these patients, we evaluated whether there was a relationship between the timing of influenza vaccination and the incidence of laboratory‐confirmed influenza, influenza diagnosed by a physician, or ILI. Results: Patients who received influenza vaccine early in the season were more likely to contract influenza or ILI than patients who were vaccinated late ( P < 0.01). Vaccinated patients who developed influenza or ILI were more likely to do so later in the season ( P < 0.01). Conclusions: HIV‐infected patients vaccinated early in the flu season were more likely to contract influenza or ILI than those vaccinated later in the season.